Cure kinetics modelling and cure shrinkage behaviour of AS4/8552 - Tuğutlu, Mehmet. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
In this work, the reaction kinetics and through-the-thickness cure shrinkage upon curing of an AS4/8552 epoxy resin system have been studied. The study included two major works. Firstly, dynamic and isothermal experiments were performed to develop a new cure kinetics model using Differential Scanning Calorimetry (DSC). In the dynamic part of the experiments, 1, 2, 3, 4, and 5K/min rates were used. In the isothermal part, 120, 140, 160, and 180◦C temperatures were applied for certain durations. The most appropriate kinetic model that produces a nearly perfect fit of the scans of all data sets corresponds to a process with a single-step parallel reaction with diffusion control. The whole curing process was treated to be composed of two cure reactions. The relationship between cure rate and degree of cure was simulated by the autocatalytic twelve-parameters model. The model is a modified version of the Sourour-Kamal equation and also involves the Rabinowitch, Arrhenius, and WLF(Williams Landel Ferry) equations. Multivariant kinetic analysis were used to evaluate the parameters. The predictions of the new model were compared with the results of isothermal experiments by focusing on the degree of cure concept. Also, the glass transition temperatures, the residual heats, and the degree of cure values for each isothermal study were noted separately. The degree of cure values of isothermal experiments can be correctly predicted using the model parameters. Secondly, the coefficient of thermal expansion, the glass transition temperatures, and the through-the-thickness cure shrinkage strain values of the unidirectional and cross-ply samples, which were precured at 120, 140, 160, and 180◦C temperatures isothermally for the durations same as the isothermal DSC experiments in the autoclave, were calculated according to the data obtained by heating from room temperature up to 250◦C and cooling back to the room temperature using a Dynamic Mechanical Analyzer (DMA). The Tg (Glass Transition Temperature) values obtained by DSC and DMA samples were compared. The strain values of XP(crossply) samples were always higher than the UD(unidirectional) samples. The Tg values were proportional to the isothermal precure temperature and did not change in accordance with the type of sample (UD or XP). After the whole cure completed, the Tg values were nearly same for all samples. The Coefficient of Thermal Expansion (CTE) values above Tg are much larger than those below Tg. Without some exceptions, the CTE values of XP samples are nearly twice of UD samples. Also, after the curing is completed, the CTE values decreases. The results showed that as the isothermal precure temperature increased the cure shrinkage strain values decreased. Two composite samples (one UD, one XP), which were heated to 120◦C and held at 120◦C for one hour, were used to investigate the through-the-thickness cure shrinkage strain values of the Manufacturer’s Recommended Cure Cycle (MRCC). Also, two completely cured composite samples (one UD, one XP) were tested to find the CTEs and Tgs of fully cured samples.
Keywords: Epoxy resins -- Curing.